COPD PREVALENCE AND CHARACTERISTICS AMONG RETIRED WORKERS - Stoleski, Sasho; Minov, Jordan; Mijakoski, Dragan; Atanasovska, Aneta; Bislimovska, Dragana; Panajotovikj Radevska, Maja; Zdraveski, David (Faculty of Medicine, Ss. Cyril and Methodius University in Skopje, 2025)
Introduction:Age and exposure to noxious particles and gases are considered as important risk factors for the development of COPD. Aim of the study:To assess the prevalence of COPD in a sample of retired persons from the Skopje region.Material and methods:We performed a cross-sectional study (prevalence study) in a sample of 392 randomly selected retired persons, 207 males and 185 females, aged 56 to 84 years. Study protocol included completion of a questionnaire and pre-and post-bronchodilator spirometry.Results:The prevalence of COPD in the whole sample was 8.7% (34/392),being non-significantly higher in men (9.1%) than in women (8.1%). The difference in COPD prevalence between smoking and non-smoking retired persons was within the borders of statistical significance (10.7% vs.7.5; P=0.084). The difference in COPD prevalence between retired persons exposed to vapors, gases, dusts, and fumes (VGDF) at their workplace during their active period and retired persons with no such exposure just missed statistical significance (9.5% vs.7.4%; P=0.073). COPD prevalence in the smoking retired persons occupationally exposed to VGDF during their active period was significantly higher than its prevalence in the smoking retired persons occupationally unexposed to VGDF during their active period (12.6% vs.8.2%; P=0.036). Conclusion: Our results confirm the role of age and exposure to noxious particles and gases in the COPD development.
Keywords: COPD; Occupational exposure; noxious particles and gases; Spirometry; Questionnaire